High-rate and high-capacity battery adopting foam current collector
By using foam current collectors and three-dimensional pore structures to fill active substances in the battery, the problem of difficulty in achieving rate performance improvement in the prior art is solved, and batteries with high energy density and high rate discharge performance are achieved, and traditional materials are overcome to improve rate when energy density decreases.
Patent Information
- Application Number
- CN202420266895.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2034-01-31
AI Technical Summary
The existing high-rate lithium-ion batteries have been close to their limits because the positive and negative electrode materials and coated surface density are difficult to further improve the rate performance. At the same time, the method of reducing the surface density to increase the rate will lead to a decrease in energy density, which cannot meet the players' pursuit of speed and explosive power. .
Using foam current collector and three-dimensional pore structure, active substances are filled to improve energy density and rate discharge performance. By using foam aluminum and foam copper as current collectors, lithium cobalt oxide and artificial graphite as active substances, combined with special electrolyte and separator design, Form a battery with high energy density and high magnification discharge performance.
While maintaining or increasing the energy density, the rate discharge performance of the battery is greatly improved, and the filling rate and current of the active substance are improved through the three-dimensional porous structure of the foam current collector, reducing polarization, and achieving higher continuous rate discharge.
Smart Images

Figure CN222355155U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the field of new energy battery manufacturing, in particular to a high-rate and high-capacity battery using a foam current collector. Background Art
[0002] High-rate lithium-ion batteries are widely used in model products such as car models, aircraft models, and gun models. Because of their large current and high power output, they can provide strong explosive power. They are widely favored by professional model competition players and amateur players, and have formed a large-scale market.
[0003] The improvement of the rate performance of high-rate batteries depends on the use of more active positive and negative electrode materials, and on lower coating surface density to reduce the current surface density, thereby improving the rate discharge performance. At present, the positive and negative electrode materials have reached their limits and it is difficult to improve them further. The current limit of the negative electrode coating surface density is about 30g / ㎡. If it continues to decrease, it cannot be produced, and scratches, foil leakage and other abnormalities will appear on the surface of the pole piece. Due to these limitations, the current rate of the model battery can basically only reach a continuous discharge rate of about 50C, which cannot be further improved, and it cannot further meet the players' pursuit of speed and explosiveness.
[0004] At the same time, improving rate performance by reducing surface density also comes at the expense of energy density. The lower the surface density, the more electrode layers there are in the same size space, and the more space is occupied by auxiliary materials such as foil and diaphragm that do not provide capacity, which means lower energy density.
[0005] Improving the activity of positive and negative electrode materials and thus improving their rate discharge performance is mainly achieved by reducing the particle size of the materials and increasing the specific surface area. This is explained by taking lithium cobalt oxide, a positive electrode active material, and graphite, a negative electrode active material. At present, the D5O of high-rate lithium cobalt oxide is about 6μm, the D99 is about 10μm, the BET is 0.3~0.5㎡ / g, and it is difficult to further reduce and apply in batches; the D5O of rate-type graphite is about 8μm, the D99 is about 23μm, and the BET is 1.7~2.5㎡ / g, which is difficult to further reduce and apply in batches. The coating surface density of the negative electrode can only be about 30g / ㎡ at present. The coating surface density is difficult to further reduce. One is due to the limitation of graphite particle size, and the other is due to the limitation of process. As mentioned before, it is difficult to further improve it. Moreover, the way to reduce the surface density also leads to a decrease in energy density.
[0006] As mentioned above, it is difficult to further increase the rate of current high-rate batteries because the positive and negative electrode materials have reached their limits and the coating process is limited. Moreover, the method of reducing the surface density to increase the rate also comes at the expense of energy density.
[0007] Therefore, there is a need for a battery that achieves higher energy density and higher sustained rate discharge performance. Utility Model Content
[0008] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the utility model is to provide a battery that achieves higher energy density and higher continuous rate discharge performance.
[0009] The technical solution adopted by the utility model to solve its technical problems is:
[0010] A high-rate and high-capacity battery using a foam current collector, comprising a shell, a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator; the positive electrode sheet and the negative electrode sheet are arranged on the shell, and the shell is provided with an electrolyte and a separator; the positive electrode sheet and / or the negative electrode sheet include a foam-like three-dimensional pore structure current collector, and an active material filled in the three-dimensional pores of the foam-like three-dimensional pore structure current collector.
[0011] As an improved solution, the positive electrode plate includes a positive electrode current collector and a positive electrode active material; the positive electrode current collector is foamed aluminum.
[0012] As an improved solution, the positive electrode active material is one or more of lithium cobalt oxide, ternary, or lithium iron phosphate.
[0013] As an improved solution, the positive electrode active material has a D50 of 5 to 7 μm, a D99 of 8 to 15 μm, a BET of 0.2 to 0.5 m2 / g, a half-cell gram capacity of >190 mAh / g, and a compaction density of 3.4 to 3.8 g / dm 3 .
[0014] As an improved solution, the negative electrode plate includes a negative electrode current collector and a negative electrode active material; the negative electrode current collector is foam copper or foam nickel.
[0015] As an improved solution, the negative electrode active material is one or more of artificial graphite, modified graphite, silicon carbon or silicon oxygen.
[0016] As an improved solution, the negative electrode active material artificial graphite has a D50 of 7-9 μm, a D99 of 10-25 μm, a BET of 1.7-2.5 m2 / g, a half-cell gram capacity of >330 mAh / g, and a compaction density of 1.25-1.45 g / dm 3 .
[0017] As an improved solution, the diaphragm is one of a dry membrane, a wet membrane, a coated ceramic membrane, and a gel membrane.
[0018] As an improved solution, the diaphragm is a wet-process base membrane with a porosity of 49±3(%) and an air permeability of 120±30s / 100mL.
[0019] As an improved solution, the electrolyte solvent is EC, PC, DMC, and the lithium salt is LiPF6.
[0020] Compared with the prior art, the beneficial effects of the utility model are:
[0021] The energy density is increased while the rate is increased. Or the energy density is not lost while the rate is increased.
[0022] The use of foam current collectors, including positive and negative current collectors, can greatly improve the energy density while maintaining the same rate discharge capacity, and greatly improve the rate discharge performance while maintaining the same energy density.
[0023] The special three-dimensional structure of the foam current collector gives it many excellent properties that are different from traditional materials. It is these properties that make it very suitable for use in the design of new battery current collectors:
[0024] High permeability: The permeability of copper foam can reach more than 98%, and it has an almost fully transparent structure, so it is easier to combine with other materials to play a special role and improve battery performance;
[0025] Large specific surface area: Under the same porosity, it has the largest specific surface area compared with other porous materials, up to 1㎡ / g or more; high porosity and uniform pore structure: The porosity of foam copper is as high as 95%, which is a three-dimensional porous and transparent structure with good metal strength.
[0026] The reasons why the foam current collector can improve the energy density and rate discharge performance are:
[0027] 1. The foam current collector has a three-dimensional porous structure. The active material can be filled into the pores, instead of being intelligently coated on the surface like an ordinary smooth current collector. The active material is filled in the three-dimensional pores, which not only increases the filling rate, improves the space utilization rate, and increases the capacity; it also helps to absorb and retain the electrolyte, and also helps to evenly distribute the current, providing more and shorter paths for the transmission of electrons between the active material and the current collector, reducing polarization, reducing DCR, and thus improving the rate performance;
[0028] 2. For ordinary current collector foil, active materials can only be distributed on its surface. There is a large difference in the length of the transmission path of the coating layer close to the current collector and far away from the current collector. This difference leads to more serious polarization during charge and discharge, making electron transmission uneven and causing polarization to increase. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The utility model is a cross-sectional structural diagram of a high-rate and high-capacity battery using a foam current collector.
[0030] Figure 2 The utility model is a schematic structural diagram of a foam current collector of a high-rate and high-capacity battery using a foam current collector.
[0031] Figure 3 The utility model discloses a 50C rate discharge curve of a high-rate and high-capacity battery using a foam current collector.
[0032] Figure 4 The utility model discloses a 60C rate discharge curve of a high-rate and high-capacity battery using a foam current collector.
[0033] Figure 5 The utility model discloses a 100C rate discharge curve of a high-rate and high-capacity battery using a foam current collector.
[0034] Among them, 1: shell; 2: positive electrode plate; 3: negative electrode plate; 4: electrolyte; 5: diaphragm; 6: foam-like three-dimensional pore structure current collector; 7: active material. DETAILED DESCRIPTION
[0035] The present invention is further described with reference to the accompanying drawings and embodiments:
[0036] The present invention is further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0037] It should be noted that when a component / part is referred to as being "set on" another component / part, it may be directly set on the other component / part or there may also be an intermediate component / part. When a component / part is referred to as being "connected / coupled" to another component / part, it may be directly connected / coupled to the other component / part or there may be an intermediate component / part at the same time. The term "connection / coupling" as used herein may include electrical and / or mechanical physical connections / couplings. The term "includes / comprising" as used herein refers to the presence of a feature, step or component / part, but does not exclude the presence or addition of one or more other features, steps or components / parts. The term "and / or" as used herein includes any and all combinations of one or more relevant listed items.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application. In addition, in the description of the present application, the terms "first", "second", etc. are only used to describe the purpose and distinguish similar objects, and there is no sequential order between the two, nor can they be understood as indicating or implying relative importance. In addition, in the description of the present application, unless otherwise stated, the meaning of "plurality" is two or more.
[0039] The features described herein may be implemented in different forms and should not be interpreted as being limited to the examples described herein. Rather, the examples described herein have been provided only to illustrate some of the many possible ways of implementing the methods, devices and / or systems described herein that will be apparent after understanding the disclosure of the present application.
[0040] As used herein, the term "and / or" includes any one of the associated listed items and any combination of any two or more items.
[0041] The terms used herein are only used to describe various examples and are not used to limit the present disclosure. Unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. The terms "include", "comprise" and "have" list the stated features, quantities, operations, components, elements and / or their combinations that exist, but do not exclude the existence or addition of one or more other features, quantities, operations, components, elements and / or their combinations.
[0042] Variations in the shapes shown in the drawings may occur due to manufacturing techniques and / or tolerances. Therefore, the examples described herein are not limited to the specific shapes shown in the drawings but include variations in shapes that occur during manufacturing.
[0043] The features of the examples described herein may be combined in various ways that will be apparent after understanding the disclosure of the present application. In addition, although the examples described herein have various configurations, other configurations are possible as will be apparent after understanding the disclosure of the present application.
[0044] Implementation case 1:
[0045] Preparation of single lithium-ion battery
[0046] Aluminum foam is used as the positive electrode current collector, and copper foam is used as the negative electrode current collector.
[0047] The positive electrode active material is lithium cobalt oxide, D50 is 5-7μm, D99 is 8-15μm, BET is 0.2-0.5㎡ / g, half-cell gram capacity is >190mAh / g, and compaction density is 3.4-3.8g / dm 3 .
[0048] The negative electrode active material is artificial graphite, with a D50 of 7-9 μm, a D99 of 10-25 μm, a BET of 1.7-2.5 m2 / g, a half-cell capacity of >330 mAh / g, and a compaction density of 1.25-1.45 g / dm 3 .
[0049] The electrolyte used is a 12s / m electrolyte, the main solvents are EC, PC, DMC, the lithium salt is LiPF6, and some negative electrode film-forming additives and high-temperature improvement additives are added.
[0050] The diaphragm used has a porosity of 49±3(%) and a wet-process base membrane with an air permeability of 120±30s / 100mL.
[0051] The battery model is P7330048.
[0052] Positive electrode formula, lithium cobalt oxide: conductive agent: binder = 92:5:3,
[0053] Negative electrode formula, graphite: conductive agent: binder: thickener = 95.0:1.5:1.5:2.
[0054] The positive electrode solvent is NMP, and the negative electrode solvent is deionized water.
[0055] The above is the experimental group scheme, while the control group uses conventional aluminum foil and copper foil. Other materials are the same as those of the experimental group.
[0056] 1) Ingredients: Mix the ingredients according to the above formula ratio, sieve out the slurry and set aside;
[0057] 2) Coating: Coating is performed on a continuous blade coating machine and then dried in an oven;
[0058] 3) Film rolling: Roll the dried coil to compact the positive and negative electrode sheets;
[0059] 4) Sheet making: The electrode sheet after film rolling is sheeted using a rubber plate die. The negative electrode sheet is 0.4 mm wider than the positive electrode sheet, and the negative electrode sheet is 1.0 mm longer than the positive electrode sheet.
[0060] 5) Laminated packaging: The laminated body is made by laminating process. The negative electrode has one more layer than the positive electrode. The outer layer is the negative electrode sheet. The lamination must be carried out in a low humidity workshop with a humidity of ≤2% RH.
[0061] 6) Pole ear welding: The positive pole ear is an aluminum pole ear of 0.2*8*18mm, and the negative pole ear is a nickel pole ear of 0.2*8*18mm. Use an ultrasonic welder to weld the pole ear and the laminated body pole handle firmly;
[0062] 7) Packaging: Use 1Showa 11 dry aluminum plastic film packaging;
[0063] 8) Baking: Baking in a high vacuum oven at 90°C for 12 hours;
[0064] 9) Injection: Inject electrolyte at a rate of 3.8 g / Ah;
[0065] 10) Formation: High temperature and pressure formation, temperature is 45°C, pressure is 0.5Mpa;
[0066] 11) Molding: First, vacuum the excess electrolyte and the gas generated by the formation, then cut off the remaining edges and complete the folding molding.
[0067] 12) After the battery is formed, arrange rate performance testing, verification and comparison.
[0068] Experimental data: Model P7330048-3.7V
[0069]
[0070] In summary, after reading the utility model document, ordinary technicians in this field can make various other corresponding transformation schemes based on the technical scheme and technical concept of the utility model without creative mental labor, and different application scenarios all fall within the scope of protection of the utility model.
Claims
1. A high rate and high capacity battery using a foam current collector, characterized in that: The invention comprises a shell (1), a positive electrode sheet (2), a negative electrode sheet (3), an electrolyte (4), and a separator (5); the positive electrode sheet (2) and the negative electrode sheet (3) are arranged on the shell (1), and the shell (1) is provided with an electrolyte (4) and a separator (5); the positive electrode sheet (2) and / or the negative electrode sheet (3) comprises a foam-like three-dimensional pore structure current collector (6), and an active material (7) filled in the three-dimensional pores of the foam-like three-dimensional pore structure current collector (6).
2. The high-rate and high-capacity battery using a foam current collector according to claim 1, characterized in that: The positive electrode plate (2) comprises a positive electrode current collector and a positive electrode active material (7); the positive electrode current collector is foamed aluminum.
3. The high-rate and high-capacity battery using a foam current collector as claimed in claim 2, characterized in that: The positive electrode active material (7) has a D50 of 5-7 μm, a D99 of 8-15 μm, a BET of 0.2-0.5 m2 / g, a half-cell gram capacity of >190 mAh / g, and a compaction density of 3.4-3.8 g / dm³.
4. The high-rate and high-capacity battery using a foam current collector according to claim 1, characterized in that: The negative electrode plate (3) comprises a negative electrode current collector and a negative electrode active material (7); the negative electrode current collector is foam copper or foam nickel.
5. The high-rate and high-capacity battery using a foam current collector as claimed in claim 4, characterized in that: The negative electrode active material (7) is artificial graphite, with a D50 of 7-9 μm, a D99 of 10-25 μm, a BET of 1.7-2.5 m2 / g, a half-cell gram capacity of >330 mAh / g, and a compaction density of 1.25-1.45 g / dm³.
6. The high-rate and high-capacity battery using a foam current collector according to claim 1, characterized in that: The diaphragm (5) is one of a dry membrane, a wet membrane, a coated ceramic membrane, and a gel membrane.
7. The high-rate and high-capacity battery using a foam current collector according to claim 6, characterized in that: The diaphragm (5) is a wet-process base membrane with a porosity of 49±3% and an air permeability of 120±30s / 100mL.